Assessment of Water Quality in Rural Drinking Water Supply Systems in Yogyakarta - Rif'atunnisa; Ni Nyoman Nepi Marleni; Budi Kamulyan (Poltekkes Kemenkes Surabaya, 2026)
Access to safe drinking water in rural areas remains a global public health challenge, especially in Indonesia. This study evaluates the water quality of the Tirta Wening Rural Drinking Water Supply System in Kulon Progo Regency, Special Region of Yogyakarta, which operates two treatment facilities: SPAM 1 and SPAM 2. In order to assess each network’s compliance with national quality standards for drinking water, a total of twelve quality parameters were measured at six different water sampling points. These parameters include: (1) physical properties—temperature, turbidity, color, odor, total dissolved solids/TDS; (2) chemical concentrations—pH, nitrite, nitrate, iron, manganese; (3) microbiological contaminations—E. coli, total coliform. The results show that the physical and chemical parameters have already aligned with their standards, except for TDS and manganese concentrations. There are two sampling points in SPAM 1 and five points in SPAM 2 that have a higher TDS than the permissible concentration of 300 mg/L. The manganese concentrations exceed the maximum standard of 0.1 mg/L at one sampling point in SPAM 1 and three points in SPAM 2. In terms of microbiological parameter, E. coli contamination was found at four sampling points in SPAM 1 and all points in SPAM 2, and total coliform exceeds 300 CFU/100 mL at almost all the sampling points. These findings highlight the need for improved treatment, routine monitoring, and household-level solutions to meet national drinking water quality standards.